A Key Silencing Histone Mark on Chromatin Is Lost When Colorectal Adenocarcinoma Cells Are Depleted of Methionine by Methionine γ-Lyase - Raboni, Samanta; Montalbano, Serena; Stransky, Stephanie; Garcia, Benjamin A.; Buschini, Annamaria; Bettati, Stefano; Sidoli, Simone; Mozzarelli, Andrea (Frontiers in Molecular Biosciences, 2021)
Methionine is an essential amino acid used, beyond protein synthesis, for polyamine formation and DNA/RNA/protein methylation. Cancer cells require particularly high methionine supply for their homeostasis. A successful approach for decreasing methionine concentration is based on the systemic delivery of methionine gamma-lyase (MGL), with in vitro studies demonstrating its efficacy in cancer therapy. However, the mechanisms explaining how cancer cells suffer from the absence of methionine more significantly than non-malignant cells are still unclear. We analyzed the outcome of the human colorectal adenocarcinoma cancer cell line HT29 to the exposure of MGL for up to 72 hours by monitoring cell viability, proteome expression, histone post-translational modifications and presence of spurious transcription. The rationale of this study was to verify whether reduced methionine supply would affect chromatin decondensation by changing the levels of histone methylation and, therefore, increasing genomic instability. MGL treatment showed a time-dependent cytotoxic effect on HT29 cancer cells, with an IC50 of 30 µg/ml, while Hs27 normal cells were less affected, with an IC50 of > 460 µg/ml. Although the levels of total histone methylation were not altered, a loss of the silencing histone mark H3K9me2 was observed, as well as a decrease in H4K20me3. Since H3K9me2/3 decorate repetitive DNA elements, we proved by qRT-PCR that MGL treatment leads to an increased expression of major satellite units. Our data indicate that selected histone methylation marks may play major roles in the mechanism of methionine starvation in cancer cells, proving that MGL treatment directly impacts chromatin homeostasis.